The biological clock: age, risk, and the biopolitics of reproductive time - Yopo Díaz, Martina (Sex roles, 2021)
The present article explores the social and subjective dimensions of the biological clock and its implications for reproductive time through a qualitative study based on 40 life story interviews of women from Santiago de Chile. Although the narrative of the biological clock has become a prevalent frame for addressing reproductive time in the context of late childbearing, age-related infertility, and the use of assisted reproductive technologies, few studies engage in an in-depth analysis of the biological clock—its boundaries, dynamics, and the particular ways in which it shapes women’s views and experiences of reproductive time. The present article aims to advance current knowledge on the intersection of time, reproduction, and biopolitics by arguing that the biological clock regulates reproductive time by shaping the boundaries and dynamics of female fertility through the clock. By determining reproductive time as quantitative, standardised, linear, and irreversible and by outlining the passing of time through pressure, risk, and burden, the biological clock determines when it is possible and desirable to have children and regulates reproduction, gender, and the female life course. These findings highlight the importance of critically addressing the narrative of the biological clock and its implications for women’s views and experiences of reproductive time.